PELAKSANAAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) MENURUT PERATURAN MENTERI AGRARIA DAN TATA RUANG/KEPALA BADAN PERTANAHAN NASIONAL REPUBLIK INDONESIA NOMOR 6 TAHUN 2018 (CONTOH KASUS: DESA LEMBANGSARI KECAMATAN RAJEG KABUPATEN TANGERANG) - Wiranti Agustina Ningrum; Gunawan Djajaputra (Fakultas Hukum Universitas Tarumanagara, 2021)
Land has a high economic value and can be the obligation of every individual to maintain and maintain its existence as an object that is considered very economical on the grounds that land has benefits for the implementation of development, not least land can cause various kinds of problems for humans so that its use must be controlled. as well as possible so that new problems do not arise in people's lives. The provisions in Article 33 paragraph (3) of the 1945 Constitution of the Republic of Indonesia which states